Changes in concentrations of tau-reactive antibodies are dependent on sex in Alzheimer's disease patients - Krestova, Michala; Ricny, Jan; Bartos, Ales (Journal of neuroimmunology, 2018)
The presence of pre-existing natural antibodies against Alzheimer's disease (AD) pathological proteins might interfere with immune responses to therapeutic vaccination with these proteins. We aimed to compare levels of antibodies in CSF and serum: We observed higher reactivity of natural tau-reactive antibodies towards phosphorylated bovine tau protein than to human recombinant (non-phosphorylated) tau protein. Males with MCI-AD had higher amounts of these antibodies than corresponding controls. Concentrations of antibodies were lower in females with the MCI-AD than in control females. These findings may have implications for tau vaccination trials.
Keywords: Alzheimer's disease; senioři; Mild cognitive impairment; tau Proteins; Cognitive Dysfunction; Reproducibility of Results; specificita protilátek; proteiny tau; demence; reprodukovatelnost výsledků; Phosphoproteins; Phosphorylation; Post-translational modification; fosfoproteiny; rekombinantní proteiny; Middle Aged; mužské pohlaví; posttranslační úpravy proteinů; Alzheimer Disease; Recombinant Proteins; skot; Sex; ženské pohlaví; Protein Processing, Post-Translational; zvířata; Humans; Sex Characteristics; autoprotilátky; kognitivní dysfunkce; Dementia; Cattle; lidé středního věku; Species Specificity; Tau protein; Antibody Specificity; Alzheimerova nemoc; fosforylace; druhová specificita; pohlavní dimorfismus; Aged; Female; Autoantibodies; lidé; Male; Antibody; Animals